KERAJINAN SULAMAN DI NAGARI KOTO BARU SIMALANGGANG KECAMATAN PAYAKUMBUH KABUPATEN LIMA PULUH KOTA - Fitri, Fitri; Zahri, Wildati; Izwerni, Izwerni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
The focuses of the research are : 1) various kind of embroidery in Koto Baru Simalanggang; 2) the shape of design in Koto Baru Simalanggang; 3) the technique of embroidery in Koto Baru Simalanggang. The research is aimed to describe : 1) various kind of embroidery in Koto Baru Simalanggang; 2) the shape of design in Koto Baru Simalanggang; 3) the technique of embroidery in Koto Baru Simalanggang. The type of the research is qualitative research. The informan of this research are the entrepreneurs of embroidery in Nagari Koto Baru Simalanggang. The tecnigue of collecting data is gained through : 1) observation; 2) interview; 3) documentation. The result of this research is based on the observation and the interview with the embroidery entrepreneurs in Koto Baru Simalanggang. The type of embroidery in Koto Baru Simalanggang such as : needlepoint liquid suji, flat embroidery, embroidered fantasi, emboroidered shadow, embroidered arise, ribbon embroidery, attaching lace, attaching sequin, attaching rose, attaching tulips, and attacing the stars. The design in Koto Baru Simalanggang are generally from the nature like ; stalk, leaf, grass, jasmine, rose, orchid, sunflower, tulips, ylang flowers, lotus, trumpet flower, daisies, grape and the other design like animal such as : butterfly. The decorative pattern in Koto Baru Simalanggang : sprinkle pattern, the placement of the design : table cover, curtain, bedcover, cloth, etc, the pattern of filling the shape of triangle, the placement of the design : table cover, pocket, sleeve tops, etc, the pattern of filling square area, the placement of the design : table cover, filling the edge, front center and free pattern , the placement of the design : free as longus it doesnot bother the sewing of the structure of the thing. The embroidery technique based on the embroidery technique at Koto Baru Simalanggang are : hand embroidery, such as : needlepoint liquid suji, flat embroidery, embroidered fantasi, emboroidered shadow, embroidered arise, ribbon embroidery, attaching lace, attaching sequin, attaching rose, attaching tulips, attacing the stars and machine embroidery sush as : needlepoint liquid suji, and satin embroidery. Based on the technique of the group of the embroidery in Koto Baru Simalanggang are : the decorative embroidery technique sush as : needlepoint liquid suji, flat embroidery, embroidered fantasi, emboroidered shadow, embroidered arise, ribbon embroidery and atfachment embroidery techniques such as : attaching lace, attaching sequin, attaching rose, attaching tulips, and attacing the stars. Kata kunci: sulaman, Koto Baru Simalanggang